Challenging Binary Frameworks: An Experimental Study on Cognitive Bias and the 'Othering' Effect in Cultural Competence Training - Ecirli, Ahmet (European Journal of Social Science Education and Research, 2025)
As globalization intensifies, cultural training for managers and students has become standard practice. This paper critiques the dominant pedagogical approach, which relies on positivist, dichotomous cultural models. We argue that these binary frameworks may function as cognitive heuristics that inadvertently trigger rapid, intuitive "System 1" thinking, thereby reinforcing stereotypes and fostering a sense of "Othering." This study employed a pre-test/post-test experimental design with 210 business students randomly assigned to one of three groups: a Dichotomy-Based Training, a Reflexive Training based on postcolonial critique, or a Control Group. Cognitive bias was measured using a custom Implicit Association Test (IAT) and a vignette-based survey of stereotypical attributions. Analysis of Covariance (ANCOVA) revealed a significant, detrimental effect of the dichotomy-based training, which led to a statistically significant increase in both implicit bias and explicit stereotyping compared to the other groups. The findings provide robust empirical evidence that the very tools used to promote intercultural understanding may inadvertently cause harm, offering a clear mandate for educators to adopt more nuanced, reflexive pedagogical approaches.
Keywords: Cognitive Bias, Cultural Training, Stereotyping, Dichotomous Frameworks, Intercultural Competence, System 1/2 Thinking, Othering, Postcolonial Theory, Management Education